Regioselective Approach to 5-Carboxy-1,2,3-triazoles Based on Palladium-Catalyzed Carbonylation - Kotovshchikov, Yury N.; Latyshev, Gennadij V.; Beletskaya, Irina P.; Lukashev, Nikolay V. (Synthesis, 2018)
A regioselective two-step approach to 5-carboxy-1,2,3-triazoles based on palladium-catalyzed carbonylation has been developed. The protocol utilizes readily available 5-iodotriazoles as starting materials. The obtained products were used in the syntheses of fused heterocycles as well as derivatization of the steroidal hormone cortexolone.
Keywords: 1,2,3-triazole; carbonylation; catalysis; palladium; copper